Seroprevalence of foot and mouth disease in small ruminant population of Tamil Nadu - M.Madhanmohan; S.B.Nagendrakumar; V.A.Srinivasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Foot and mouth disease is an acute febrile highly contagious disease of cloven footed animals. India has a sizable proportion of small ruminants (135.17 million goats and 65.0 million sheep). Tamil Nadu, the eleventh largest state in India has a sizable proportion of sheep and goat populations (7.36 million sheep and 6.02 million goats). Sub-clinically infected small ruminants may pose a threat to cattle and buffalo in integrated livestock system. Small ruminants are neglected in FMD surveillance and control strategies in the country. In the present study, serological investigations against FMD were carried out to generate data on antibody prevalence in sheep and goat population of Tamil Nadu. Overall, 21.4% of sheep (83 out of 387 samples) and 23.5% of goats (81 out of 345 samples) tested were positive for FMD NSP antibodies and 14.7% of sheep and 18.3 % goats were positive for antibodies against virus structural proteins. The current study demonstrated the seroprevalence of FMD in the sheep and goat population of Tamil Nadu and suggests the need for surveillance activities and FMD control by vaccination in small ruminants alongside large ruminant population.